2016
DOI: 10.1007/s11999-016-4830-3
|View full text |Cite
|
Sign up to set email alerts
|

Medical School Experiences Shape Women Students’ Interest in Orthopaedic Surgery

Abstract: Successful recruitment of women to orthopaedic surgery may be improved by early exposure and access to role models, both of which will help women students' perceptions of their role in field of orthopaedic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 11 publications
1
117
1
2
Order By: Relevance
“…As CTI® is a European based journal, the fact that it is the leader in female authorship is likely due to the fact that Europe had some of the greatest increases in female authorship over time. Conversely, another explanation for differences in female authorship is that JOR® is more closely related to orthopaedic surgery, and it is well known that there is a significant gender disparity in that surgical specialty [39].…”
Section: Discussionmentioning
confidence: 99%
“…As CTI® is a European based journal, the fact that it is the leader in female authorship is likely due to the fact that Europe had some of the greatest increases in female authorship over time. Conversely, another explanation for differences in female authorship is that JOR® is more closely related to orthopaedic surgery, and it is well known that there is a significant gender disparity in that surgical specialty [39].…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] High income United States Correlation study n = 384 (189/195) 49% University-sponsored 2016 Medical School Experiences Shape Women Students' Interest in Orthopaedic Surgery. [ 38 ] High income United States United Kingdom Systematic Review Not reported 2016 Mentorship as Experienced by Women Surgeons in Japan. [ 52 ] High income Japan Questionnaire n = 55 100% Not reported 2016 Women in academic surgery: why is the playing field still not level?…”
Section: Resultsmentioning
confidence: 99%
“…Chair persons of these departments accept greater responsibility for assuring that female students obtain as high a quality clerkship experience as do male students. 34 O'Conner 35 reported that orthopedic surgery has the lowest percentage of women in any residency program and that the medical student experience affects female interest in the specialty. He suggests that having role models of the same gender and preclinical exposure to the field and improving gender representation among residents and faculty will enhance recruitment.…”
Section: Expert Reviewsmentioning
confidence: 99%
“…He suggests that having role models of the same gender and preclinical exposure to the field and improving gender representation among residents and faculty will enhance recruitment. 35 Obstetrics/gynecology educators must consider methods of encouraging patients to accept medical student participation, regardless of gender; obstetrics/gynecology faculty members and residents must be sensitive to subtle forms of gender bias and ensure equal inclusion for both male and female medical students. Faculty members must improve their attitudes toward male students, to encourage them and make them feel welcome in the clinical area.…”
Section: Expert Reviewsmentioning
confidence: 99%